FDTD simulation of the optical properties for gold nanoparticles. (16th December 2020) - Cheng, Lin; Zhu, Guixian; Liu, Gannan; Zhu, Lianqing
Abstract: The optical properties of gold nanoparticles such as strong extinction and surface plasmon resonance can be adjusted by altering the structure, which was used widely in the surface enhanced Raman scattering (SERS). In this paper, the optical properties of gold nanoparticles were investigated by using the Finite-Difference Time-Domain (FDTD) method. The influences of AuNP-size and NP-NP-spacing on the local electric field and extinction properties were analyzed in detail. The results showed that the electric field intensity of AuNPs increased rapidly with the increasing size. Meanwhile, the formant appeared blue shift and the peak intensity increased first and then decreased with the increase of NP-NP-spacing. The theoretical calculation results are concordant with experimental results. The FDTD simulation results of this paper have a guiding significance in SERS areas.